Modelling the Peak Cutting Temperature During High-Speed Machining of AISI 1045 Steel - BURNS, Timothy J.; MATES, Steven P.; RHORER, Richard L.; WHITENTON, Eric P.; BASAK, Debasis (Engineering Transactions, 2012)
This paper presents new experimental data on AISI 1045 steel from the NIST pulse-heated Kolsky Bar Laboratory. The material is shown to exhibit a stiffer response to compressive loading when it has been rapidly preheated, than it does when it has been heated using a slower preheating method, to a testing temperature that is below the eutectoid temperature. It is argued, using a simple model for heat generation in the workpiece and the tool during machining, due to Tlusty, that this work has important implications for the modelling of high- speed machining operations. Based on the experimental data, a modification is recommended of the well-known Johnson-Cook constitutive model of Jaspers and Dautzenberg for this material, in order to achieve improved predictions of the peak cutting temperature in machining.